ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN TIKET PERJALANAN - Prastika, Retma (Universitas Mercu Buana, 2022)
Theories in influencing factors explain some of the factors therein; cultural factors, social factors, personal factors and psychological factors. These factors are to find out the factors that influence and are dominant in making decision to purchase travel tickets on Tiket.com. This type of research used in this study is descriptive in a quantitative approach. The method used is a survey research on ticket.com consumers in Jakarta. Where researchers collect data premiere that is distributing questionnaires to respondents as many as 100 using purposive sampling techniques. Based on the results of the study show that cultural factors influence the decision to purchase tickets as much as 58% agree that it is a personal need that includes basic values, social factors as much as 66% disagree with the outdated influence on ticket purchase decision making, then personal factors as much as 71 % agreed that job needs influenced ticket purchasing decisions, while psychological factors as much as 54% agreed with the services provided, 67% strongly agreed with data confidentiality and 66% agreed that there was never an error when making payments.